Effect of AMT on Responsive Supply Chain Strategy, Pull System and Responsiveness to Market - Díaz Reza, José Roberto (2020)
This paper presents a model of structural equations in which four variables (advanced manufacturing technology, Pull system, responsiveness to market and, responsive supply chain strategy) are related using six hypotheses. The objective of the research is to measure the effect that occurs between these variables and identify the most important activities that have the greatest effect on the others. The model is statistically validated with information of 254 responses to a questionnaire applied in the manufacturing industry and the partial least squares technique is used. The results indicate that advanced manufacturing technologies indirectly help companies to be able to respond to changes in demand and allow them to offer a rapid response in the changing market through the implementation of a pull system.